2019
DOI: 10.1136/oemed-2019-105772
|View full text |Cite|
|
Sign up to set email alerts
|

Environmental exposures in young adults with declining kidney function in a population at risk of Mesoamerican nephropathy

Abstract: ObjectivesThere is an epidemic of Mesoamerican nephropathy (MeN) in Central America, where sugarcane production is prominent. Numerous causes are proposed, but to date limited evidence supports any one hypothesis. A nested case–control study using biosamples from a rural, community-based follow-up study of 350 young adults from Northwest Nicaragua at risk of MeN was conducted with the aim of characterising the associations between urinary concentrations of metals, pesticides and mycotoxins from samples collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…A comprehensive review from 2017 (63) concluded that there was scarce evidence for an association, but recommended studies with adequate exposure assessment before definitely discarding pesticides as an important risk. More recently, the above-mentioned Nicaraguan community cohort did not observe an association of self-reported pesticide use and kidney dysfunction, including glyphosate, paraquat, cypermethrin and methomyl (58), and a case-control study nested in this cohort found no association between rapid decline of eGFR over two years and baseline urinary levels of 12 common pesticides or their metabolites, including 2,4-D, glyphosate, chlorpyrifos and pyrethroid insecticides (64). To date, the only suggestive finding in Mesoamerica in relation to pesticides is a 13% prevalence of CKD stage ≥3 in Las Brisas, El Salvador, similar for men and women, attributed to local groundwater contamination with toxaphene after the dismantling of a pesticide storehouse by the community (23), which suggests an isolated situation.…”
Section: Pesticides and Metalsmentioning
confidence: 64%
See 1 more Smart Citation
“…A comprehensive review from 2017 (63) concluded that there was scarce evidence for an association, but recommended studies with adequate exposure assessment before definitely discarding pesticides as an important risk. More recently, the above-mentioned Nicaraguan community cohort did not observe an association of self-reported pesticide use and kidney dysfunction, including glyphosate, paraquat, cypermethrin and methomyl (58), and a case-control study nested in this cohort found no association between rapid decline of eGFR over two years and baseline urinary levels of 12 common pesticides or their metabolites, including 2,4-D, glyphosate, chlorpyrifos and pyrethroid insecticides (64). To date, the only suggestive finding in Mesoamerica in relation to pesticides is a 13% prevalence of CKD stage ≥3 in Las Brisas, El Salvador, similar for men and women, attributed to local groundwater contamination with toxaphene after the dismantling of a pesticide storehouse by the community (23), which suggests an isolated situation.…”
Section: Pesticides and Metalsmentioning
confidence: 64%
“…In Nicaragua, lead, cadmium, and uranium were not associated with biomarkers of kidney injury or kidney function among sugarcane workers and miners, whereas total arsenic was associated with kidney injury among workers with the highest urinary levels (28). However, a longitudinal study following urinary levels of 12 metals in the Nicaraguan general population found no association with cases of rapid kidney function decline (64). A systematic assessment of the probability that metals were potentially important, concluded that this was highly unlikely, firstly because no particularly high exposures have been found in populations at risk as compared to established dose-response relationships, secondly because the clinical and histopathological presentation of CKDnt is not in accordance with the usual renal metal toxicity findings (66).…”
Section: Pesticides and Metalsmentioning
confidence: 95%
“…Further, biomonitoring studies that evaluate urinary metal concentrations in sugarcane workers before, during, and after a harvest operation remain critical to understanding and quantifying real-world exposures. The few Central America studies that have examined the relationship between exposure to nephrotoxic metals and acute or chronic renal effects have yielded varying results [ 14 , 67 , 68 , 69 ]. The fingerprint and concentration of heavy metals in the soil have likely changed due to the recent eruption of Fuego in 2018 and subsequent deposition of basaltic ash on the topsoil in the sugarcane fields.…”
Section: Discussionmentioning
confidence: 99%
“…73,74 However, recent studies and reviews report that the evidence is still inconclusive to support the presence of such environmental toxins, heat stress, or dehydration in affected patients. [75][76][77][78] Vervaet et al 38 also proposed a toxic etiological factor which acts via the calcineurin inhibition pathway based on the proximal tubular lysosomal lesions found in the Sri Lankan and Mesoamerican patients. This lesion was also found in one healthy control from Sri Lanka.…”
Section: Pathogenesis Of the Renal Lesionsmentioning
confidence: 99%